Driftcretions: The legacy impacts of driftwood on shoreline morphology. Issue 14 (20th July 2015) - Kramer, Natalie; Wohl, Ellen
Abstract: This research demonstrates how vegetation interacts with physical processes to govern landscape development. We quantify and describe interactions among driftwood, sedimentation, and vegetation for Great Slave Lake, which is used as proxy for shoreline dynamics and landforms before deforestation and wood removal along major waterways. We introduce driftcretion to describe large, persistent concentrations of driftwood that interact with vegetation and sedimentation to influence shoreline evolution. We report the volume and distribution of driftwood along shorelines, the morphological impacts of driftwood delivery throughout the Holocene, and rates of driftwood accretion. Driftcretions facilitate the formation of complex, diverse morphologies that increase biological productivity and organic carbon capture and buffer against erosion. Driftcretions should be common on shorelines receiving a large wood supply and with processes which store wood permanently. We encourage others to work in these depositional zones to understand the physical and biological impacts of large wood export from river basins. Key Points: Continued accretion of driftwood to shorelines alter morphology on large scales Driftwood‐rich shores influence ecosystems, carbon capture, and erosional buffering Rates and volumes of accretion are nontrivial for basin wood and carbon budgets